The activity of glyphosate, glufosinate-ammonium and imazapyr on Imperata cylindrica (L). Raeuschel - Mohamad, Rosli; Goh, Ching Hock (1989)
A field experiment was conducted to evaluate the effect of glyphosate, glufosinate-ammonium and imazapyr on a stand of Imperata cylindrica (L.) Raeuschel. Spray volumes of 400 1/ha and 800 1/ha were used for each chemical. Visual observation on foliage control was related to the tiller number/unit area and mass production of green foliage and fresh rhizomes. Pattern of weed succession was also recorded. All aspect of observations indicated that spray volume did not influence the effectiveness of the chemicals. Effective control of foliage (80% killed or more) of I. cylindrica was achieved with all the chemicals used, but with different rate of response. Glufosinate-ammonium (3 kg a.i./ha) provided the control within the first until the eight weeks after foliar application. In contrast, for glyphosate (1.62 kg a.e./ha) and imazappyr (0.75 kg a.e./ha) the periods were from the third and from the 14th week to the end of the experiment period (18th week), respectively. At the 18th week, when some regrowth was already evident, the dry weight of green foliage and rhizomes were significantly lower for the three herbicides compared with those for the control. Substantial increased in the density of broad-leaf weeds was observed at the end of the experiment period in the glyphosate and glufosinate-ammonium treatments. However, the change in density of the other grass weeds in all treatments were minimal. The significance of these findings were discussed.